Anti-hyperalgesic effect of (-)-α-bisabolol and (-)-α-bisabolol/β-Cyclodextrin complex in a chronic inflammatory pain model is associated with reduced reactive gliosis and cytokine modulation. (December 2019) - Fontinele, Laíza Lima; Heimfarth, Luana; Pereira, Erik Willyame Menezes; Rezende, Marília Matos; Lima, Natália Teles; Barbosa Gomes de Carvalho, Yasmim Maria; Afonso de Moura Pires, Elisana; Guimarães, Adriana Gibara; Bezerra Carvalho, Mikaella Tuanny; de Souza Siqueira Barreto, Rosana; Campos, Adriana Rolim; Antoniolli, Angelo Roberto; et al.
Abstract: Chronic pain is a continuous or recurring pain which exceeds the normal course of recovery to an injury or disease. According to the origin of the chronic pain, it can be classified as inflammatory or neuropathic. This study aimed to evaluate the antinociceptive and anti-inflammatory effect of (-)-α-bisabolol (BIS) alone and complexed with β-cyclodextrin (βCD) in preclinical models of chronic pain. Chronic pain was induced by Freund's Complete Adjuvant (FCA) or partial lesion of the sciatic nerve (PLSN). Swiss mice were treated with BIS, BIS-βCD (50 mg/kg, p.o) or vehicle (control) and mechanical hyperalgesia, thermal hyperalgesia, muscle strength and motor coordination were evaluated. In addition, levels of TNF-α and IL-10 and expression of the ionized calcium-binding adapter protein (IBA-1) were assessed in the spinal cord of the mice. The complexation efficiency of BIS in βCD was evaluated by High-Performance Liquid Chromatography. BIS and BIS-βCD reduced (p < 0.001) mechanical and thermal hyperalgesia. No alterations were found in force and motor coordination. In addition, BIS and BIS-βCD inhibited (p < 0.05) TNF-α production in the spinal cord and stimulated (p < 0.05) the release of IL-10 in the spinal cord in PLSN-mice. Further, BIS and BIS-βCD reduced IBA-1 immunostaining. Therefore, BIS and BIS-βCD attenuated hyperalgesia, deregulated cytokine release and inhibited IBA-1 expression in the spinal cord in the PLSN model. Moreover, our results show that the complexation of BIS in βCD reduced the therapeutic dose of BIS. We conclude that BIS is a promising molecule for the treatment of chronic pain. Highlights: BIS and BIS-βCD reduced mechanical and thermal hyperalgesia in inflammatory and neuropathic pain. BIS and BIS-βCD inhibited TNF-α production in the spinal cord and stimulated the release of IL-10 in the spinal cord in PLSN-mice. BIS and BIS-βCD reduced IBA-expression in the spinal cord in the PLSN model.